Percutaneous nephrostomy placement in pregnant patients: a retrospective single center experience. (4th March 2022) - Epelboym, Yan; Tivnan, Patrick; Desai, Khanant; O'Horo, Susan
Abstract: Purpose: Literature on percutaneous nephrostomy (PCN) placement in pregnant patients is limited. The purpose of this case series of 20 pregnant patients was to report short term maternal and fetal outcomes in this population. Materials and methods: A 12-year retrospective study was performed on pregnant patients undergoing PCN. Clinical indications, technical success, maternal outcome, fetal outcome, and complications were obtained from the electronic medical record. Results: Indications for PCN placement included urolithiasis (40%), congenital ureteral dysfunction in the setting of prior ureteral repair (30%), obstruction associated pain (15%), infection (10%), and ureteral injury in the setting of surgery for ovarian torsion (5%). Catheter insertion was successful in all patients ( n  = 20), with one major complication (urosepsis). Follow up data was available in 19 patients (95%). Catheters were in situ for a median of 82 days. All patients had clinical and symptomatic improvement. Emergency C-sections were required in two cases. Radiation exposure data were available in 15 of 19 patients and revealed a median fluoroscopy time of 2.8 min, median cumulative dose of 43 mGy, and median dose area product of 635 µGy × m 2 . No adverse fetal outcomes were recorded at time of delivery. Conclusion: PCN placement has good clinical results as a treatment option for ureteral obstruction in a pregnant cohort.